ANALISIS KUALITAS PRODUK PADA PROSES TWISTING DENGAN METODE SIX SIGMA DI PT. XYZ - Rastiawan, Hanan; Susandi, Dony; Perwiranegara, Agus Alamsyah (Universitas Majalengka, 2021)
The rapid development of the times in the field of information and technology has changed the way consumers perceive a product they want. In addition to the price factor chosen by consumers, the quality of a product is also taken into consideration before making a choice. Therefore, companies must make improvements and improve the quality of their production systems, if they want to get good product quality. Repair and improvement of product quality with the hope of achieving a minimum level of product defects requires a lot of money. Companies that use quality as a strategic tool will have an advantage over competing companies, because not all companies are able to achieve the best quality. This study aims to analyze product quality with the Six Sigma method at PT. XYZ. The analytical method used in this study uses the six sigma method, namely the method (DMAIC) define, measure, analyze, improve and control. The results of this study indicate that the sigma value of the product is 3.4 sigma with CTQ 1. The total production is 61,148 and defective products are 1,727. There are 4 types of defects, namely break up 1,696, falll out 21, lump 10, and un twist 0. Proposed improvements that must be done are to conduct regular training for employees, clean up machine components related to the production process, and machine maintenance. periodically.